Aging of platelets stored for transfusion. (17th August 2016) - Smethurst, Peter A.
Abstract : A goal of platelet storage is to maintain the quality of platelets from the point of donation to the point of transfusion – to suspend the aging process. This effort is judged by clinical and laboratory measures with varying degrees of success. Recent work gives encouragement that platelets can be maintained ex vivo beyond the current 5 -7 day shelf life whilst maintaining their quality, as measured by posttransfusion recovery and survival. However, additional measures are needed to validate the development of technologies that may further reduce the aging of stored platelets, or enhance their hemostatic properties.